The validation of patient knowledge questionnaire for patients with diabetes mellitus and hyperlipidemia - Saputri, Ginanjar Zukhruf; Dania, Haafizah; Faridah, Imaniar Noor; A, Faiza Chusnuni (Universitas Ahmad Dahlan, 2018)
Prevalence of Diabetes Mellitus (DM) with Hyperlipidemia increased in Indonesia, where both diseases have a risk of complications towards cardiovascular disease. DM patients with hyperlipidemia require proper management to control blood sugar, total cholesterol and LDL cholesterol. Knowledge is one of the important factors in improving adherence therapy and quality of life of DM-hyperlipidemia patients, especially in controlling blood glucose level and total cholesterol levels. This study aims to develop a patient questionnaire of DM-hyperlipidemia.The study used cross sectional method. Inclusion criteria were patients aged 18 â 70 years old, diagnosed DM-Hyperlipidemia, getting at least 1 oral antidiabetic and oral anti-cholesterol. The questionnaire item of knowledge was developed based on gudeline therapy and previous research reference. Expert validation is done on Doctor who had expert in DM and clinical psychologist. The pilot test was performed on 10 healthy patients and 10 patients of DM-hyperlipidemia who had eligible inclusion criteria. Validation of questionnaire was done on 30 patients of DM-Hyperlipidemia who undergoing therapy at outpatient clinic of PKU Muhammadiyah Hospital Yogyakarta. Data collection was done by interviewing questionnaires in patients. Analysis of data using SPSS with product moment validation test and cronbach alpha to see the reliability of questionnaire.Validation results show there are some invalid items that are in questions 9, 11, 12, 15, 16 and 17, the range of questions about knowledge about hyperlipidemia, medication and general health. Re-validation without invalid item was done and obtained value r> 0.3, with value of Cronbach alpha 0,715.The DM-Hyperlipidemia patient questionnaire was valid and reliable to measure the level of knowledge of DM patients with Dysipidemia.Â Â